2004
DOI: 10.1093/pcp/pch063
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rice PR10 Protein, RSOsPR10, Specifically Induced in Roots by Biotic and Abiotic Stresses, Possibly via the Jasmonic Acid Signaling Pathway

Abstract: Plant roots have important roles not only in absorption of water and nutrients, but also in stress tolerance such as desiccation, salt, and low temperature. We have investigated stress-response proteins from rice roots using 2-dimensional polyacrylamide-gel electrophoresis and found a rice protein, RO-292, which was induced specifically in roots when 2-week-old rice seedlings were subjected to salt and drought stress. The full-length RO-292 cDNA was cloned, and was determined to encode a protein of 160 amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(133 citation statements)
references
References 55 publications
(65 reference statements)
6
120
2
2
Order By: Relevance
“…4). Taken together, we strongly suggest that these three PR proteins may play roles in root development under water deficit other than disease resistance response (Kim et al 2001(Kim et al , 2008Hashimoto et al 2004). Concerning the induction mechanisms of PR proteins expression, especially in relation to the crosstalk between various biotic and abiotic stresses, there were only a few reports (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…4). Taken together, we strongly suggest that these three PR proteins may play roles in root development under water deficit other than disease resistance response (Kim et al 2001(Kim et al , 2008Hashimoto et al 2004). Concerning the induction mechanisms of PR proteins expression, especially in relation to the crosstalk between various biotic and abiotic stresses, there were only a few reports (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 75%
“…RSOsPR10 exhibited a significant increase in Nipponbare root after 15 h air-drying treatment, and its transcription was strongly up-regulated within 3 h (Hashimoto et al 2004). JIOsPR10 was rapidly induced by air-dried treatment in the stem, but not in the leaves (Kim et al 2008), while its expression change in rice root was not examined.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hashimoto et al [19] investigated stress-response proteins from rice roots using 2D-PAGE and found a rice protein named as RSPR10 induced specifically in roots when 2-week-old rice seedlings were subjected to salt and drought stresses. The full-length cDNA for this protein was cloned and the deduced amino-acid sequence showed a high similarity to the known sequences of PR10, PR10a/ PBZ1, and PR10b.…”
Section: Proteomic Analyses Of Rice Under Other Stressesmentioning
confidence: 99%